2004
DOI: 10.1038/sj.bmt.1704402
|View full text |Cite
|
Sign up to set email alerts
|

An unexpectedly high incidence of Epstein–Barr virus lymphoproliferative disease after CD34+ selected autologous peripheral blood stem cell transplant in neuroblastoma

Abstract: Summary:The risk of Epstein-Barr virus lymphoproliferative disease (EBV-LPD) increases with the use of highly immunosuppressive therapies. Allogeneic BMT, especially supported by T-cell-depleted stem cell products, is a risk factor for EBV-LPD. Although the risk of EBV-LPD after autologous transplantation is low, case reports of this complication in the autologous setting exist. We report a higher incidence than previously described of EBV-LPD in children undergoing sequential high-dose chemotherapy supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…However, by taking into account the clinical status at transplant, this effect was confirmed only for patients rescued while in complete remission. Thus, the present results do not support the need for a generalized use of purging procedures, also in view of the increased risk of EBV-related lymphoproliferative disorders in CD34 + -transplanted patients (24). TH and GD2-s quantitative RT-PCR assays have already been used to detect neuroblastoma cell contamination (19, 20, 25 -28); however, this is the first study in which the two assays were done simultaneously on PBSC samples.…”
Section: Discussionmentioning
confidence: 43%
“…However, by taking into account the clinical status at transplant, this effect was confirmed only for patients rescued while in complete remission. Thus, the present results do not support the need for a generalized use of purging procedures, also in view of the increased risk of EBV-related lymphoproliferative disorders in CD34 + -transplanted patients (24). TH and GD2-s quantitative RT-PCR assays have already been used to detect neuroblastoma cell contamination (19, 20, 25 -28); however, this is the first study in which the two assays were done simultaneously on PBSC samples.…”
Section: Discussionmentioning
confidence: 43%
“…This suggests that the combination of CD34 selection and tandem transplant is more immunosuppressive than autologous SCT using unpurged PBSC. 20,31 A second study found similar results using three sequential HDC procedures. 7 : EFS at 3 years was 57%.…”
Section: Dosing Of Pbscsupporting
confidence: 64%
“…The most widely used antibody is rituximab, a chimeric murine/human monoclonal anti-CD20 antibody. Rituximab has been used as prophylaxis and treatment for PTLD after HSCT, with initial response rates between 55% and 100%, [44][45][46][47] a range that probably reflects differences in the treated patient populations. Rituximab also has activity in PTLD after SOT, in which response rates of 44% to 100% have been reported in several small studies.…”
Section: Targeting B Cellsmentioning
confidence: 99%